Current pesticide profiles in blood serum of adults in Jiangsu Province of China and a comparison with other countries. (May 2017) - Chang, Chunxin; Chen, Minjian; Gao, Jiawei; Luo, Jia; Wu, Keqin; Dong, Tianyu; Zhou, Kun; He, Xiaowei; Hu, Weiyue; Wu, Wei; Lu, Chuncheng; Hang, Bo; et al.
Abstract: Although various pesticides were used globally, the pesticides profiles in human blood serum remain largely unknown. We determined pesticide exposure profiles using solid-phase extraction and gas chromatography tandem with triple quadrupole mass spectrometry in 200 human blood serum samples from the adult population in Jiangsu Province, China. A systematic and comprehensive literature review was carried out to identify the articles investigating pesticide exposure and compare exposure data. Of the 88 pesticides, 76 were found in the blood serum of the population in Jiangsu Province. To the best of our knowledge, 58 pesticides were reported in human blood serum for the first time, and among these pesticides, parathion-methyl, pyrimethanil, fluacrypyrim, simazine, cloquintocet-mexyl and barban were debatable in more than half of the samples. By statistical comparison of the blood serum levels of pesticides between this study and other countries, we found the levels of several organochlorine pesticides were significantly higher in the female population of Jiangsu Province. Health risks related to the pesticide profiling were then revealed, which identified higher carcinogenic toxicity and teratogenic toxicity risk in the female adults of Jiangsu Province caused by organochlorine pesticide exposure. This study not only provides a high-throughput pesticide screening method for future studies of the exposome, but also presents the first human data on exposure to a number of pesticides. It may provide a knowledge database for the risk assessment and management of the pesticides.